Rapid Screening Methods for Bleeding Disorders. A Three Year Survey - Lovric, V. A; Margolis, J (Thrombosis and Haemostasis, 1964)
An adaptation of “kaolin clotting time” and prothrombin time for use on haemolysed capillary blood provided simple and sensitive screening tests suitable for use in infants and children. A survey of three year’s experience shows that these are reliable routine laboratory tests for detection of latent coagulation disorders.